Genetic covariance in immune measures and pathogen resistance in decorated crickets is sex and pathogen specific. Issue 7 (3rd May 2022) - Letendre, Corinne; Duffield, Kristin R.; Sadd, Ben M.; Sakaluk, Scott K.; House, Clarissa M.; Hunt, John
Abstract: Insects are important models for studying immunity in an ecological and evolutionary context. Yet, most empirical work on the insect immune system has come from phenotypic studies meaning we have a limited understanding of the genetic architecture of immune function in the sexes. We use nine highly inbred lines to thoroughly examine the genetic relationships between a suite of commonly used immune assays (haemocyte count, implant encapsulation, total phenoloxidase activity, antibacterial zone of inhibition and pathogen clearance) and resistance to infection by three generalist insect pathogens (the gram‐negative bacterium Serratia marcescens, the gram‐positive bacterium Bacillus cereus and the fungus Metarhizium robertsii ) in male and female Gryllodes sigillatus . There were consistent positive genetic correlations between haemocyte count, antibacterial and phenoloxidase activity and resistance to S. marcescens in both sexes, but these relationships were less consistent for resistance to B. cereus and M. robertsii . In addition, the clearance of S. marcescens was genetically correlated with the resistance to all three pathogens in both sexes. Genetic correlations between resistances to the different pathogen species were inconsistent, indicating that resistance to one pathogen does not necessarily mean resistance to another. Finally, while there is ample genetic (co)variance in immune assays and pathogen resistance, these genetic estimates differed across the sexes and many of these measures were not genetically correlated across the sexes, suggesting that these measures could evolve independently in the sexes. Our finding that the genetic architecture of immune function is sex and pathogen specific suggests that the evolution of immune function in male and female G. sigillatus is likely to be complex. Similar quantitative genetic studies that measure a large number of assays and resistance to multiple pathogens in both sexes are needed to ascertain if this complexity extends to other species. Abstract : Most empirical work on insect immunity has come from phenotypic studies; little is known about the genetic architecture of immune function. These findings show the genetic architecture of immune function to be sex‐ and pathogen‐specific in G. sigillatus, which suggests the evolution of immune function is likely to be complex.